Growth and Productivity of Acacia Hybrids on Degraded Forest Lands and other Wastelands in Western Ghats Region of Karnataka - Amanulla, B. K. Mohamed; Jayakumar, M. N.; Torvi, R. K. (Indian Forester, 2004)
Acacia species trials in MPM have given rise to open pollinated Acacia hybrids from the cross between Acacia auriculiformis and Acacia mangium. They are found to be well adapted to the hot humid conditions of Western Ghats in Karnataka. Acacia hybrids originated from Acacia mangium mother are designated as Mangi-auriculis and those originated from A. auriculiformis as ’Auriculi-mangis’. The growth performance of Mangi-auriculis is closely monitored since 1992 and the wood analysis has indicated that, the wood is suitable for pulp and paper production. Mass production of Acacia hybrid propagules is done through simple and cheap technology and large-scale clonal plantations are established. The MAI of Acacia hybrid in clonal plantation is 32m3 in 5th year whereas the MAI of Acacia auriculiformis is 16m3 at the end of 8 years. It is predicted that Acacia hybrid clonal plantations can achieve a MAI of 40 to 45m3 at the end of 8 years. Clone Ã— site interaction trials are undertaken in both wet and dry zone to choose sitespecific clones for higher productivity. MPM has drawn future strategies in the field of Tree improvement and Tree breeding to further improve the productivity of plantations. The growth potential of Acacia hybrids and their role in plantation programme are discussed in this paper.